2020
DOI: 10.1038/s41598-020-63644-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of sarcopenia in patients with colorectal liver metastases undergoing hepatic resection

Abstract: The prognostic significance of sarcopenia has been widely studied in different cancer patients. This study aimed to analyze the influence of sarcopenia on long-term survival in patients with colorectal liver metastasis (CRLM) undergoing hepatic resection. A retrospective analysis of 182 patients undergoing hepatic resection for CRLM was performed. Sarcopenia was determinedusing the Hounsfield unit average calculation (HUAC), a measure of muscle quality-muscledensity at preoperative abdominal computed tomograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 32 publications
1
22
0
1
Order By: Relevance
“…Studying these easily accesible variables as PMI, IMAC or visceral-to-subcutaneous adipose tissue area ratio (VSR), we can conclude that application of these indexes could be a keypoint in the perioperative management, but seems to be not effective in all malignant diseases. Based on several studies with patients undergoing liver resection for colorectal metastases the sarcopenia expressed by preoperative quality and quantity of skeletal muscle and visceral adiposity were not predictors of poor prognosis [ 43 , 44 ] and also sarcopenia is not a significant risk factor of overall and recurrence free survival [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studying these easily accesible variables as PMI, IMAC or visceral-to-subcutaneous adipose tissue area ratio (VSR), we can conclude that application of these indexes could be a keypoint in the perioperative management, but seems to be not effective in all malignant diseases. Based on several studies with patients undergoing liver resection for colorectal metastases the sarcopenia expressed by preoperative quality and quantity of skeletal muscle and visceral adiposity were not predictors of poor prognosis [ 43 , 44 ] and also sarcopenia is not a significant risk factor of overall and recurrence free survival [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sample size of the included studies ranged from 47 to 539 patients. [15][16][17][18][19][20][21][22][23][24][25] Median follow-up ranged between 21 and 74 months. Four studies did not report on follow-up duration.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…16,17,22,23 Median or mean follow-up did not exceed 36 months in five studies. 15,[18][19][20]25 None of the studies reported significant differences in tumour characteristics between the sarcopenic and nonsarcopenic patients. The baseline characteristics of the sarcopenic and non-sarcopenic groups in the various studies are displayed in the supplementary materials, table 4.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations